2015
DOI: 10.7150/jca.10890
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose, Low Cost Estradiol Pellets Can Support MCF-7 Tumour Growth in Nude Mice without Bladder Symptoms

Abstract: MCF-7 cells are a slow growing estrogen receptor (ER) positive human breast cancer cell line that is commonly used to model estrogen responsive breast cancer cell growth in-vitro and tumour growth in-vivo. These tumours require estrogen supplementation, and in-vivo doses of between 0.72mg and 2mg estradiol pellets are commonly implanted in the dorsal flank of ovariectomised, immunocompromised mice. We wanted to grow MCF-7 tumours in immunocompromised mice without the need to be ovariectomised. When we treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 13 publications
(13 reference statements)
3
26
0
2
Order By: Relevance
“…This is in contrast to the mouse model, where recipients continuously received estrogen via a silastic implant, enabling proliferation of the lesions [9]. These implants, however, are also associated with urinary retention and bladder cystitis [32], two phenotypes that might interfere with the endometriosis-associated pain measurements. By relying on the natural estrus cycle, the use of estrogen pellets becomes redundant, thus evading these interfering bladder pain phenotypes.…”
Section: Discussionmentioning
confidence: 95%
“…This is in contrast to the mouse model, where recipients continuously received estrogen via a silastic implant, enabling proliferation of the lesions [9]. These implants, however, are also associated with urinary retention and bladder cystitis [32], two phenotypes that might interfere with the endometriosis-associated pain measurements. By relying on the natural estrus cycle, the use of estrogen pellets becomes redundant, thus evading these interfering bladder pain phenotypes.…”
Section: Discussionmentioning
confidence: 95%
“…6 ). Of importance, both E2 and drug concentrations used in these studies were within physiological and therapeutic ranges [ 33 – 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We 17 and others 18 , 19 have reported that the human MCF7 (ER+) cell line is non-proliferative in the lung and bone and induces little osteolytic bone destruction, and have proposed this cell line as a clinically relevant model of tumor dormancy. Previous literature reports that MCF7 cells require exogenous 17β-estradiol (E2) to form orthotopic tumors and bone metastases 20 , 21 ; however, E2 results in a dramatic increase in bone volume 22 and perturbation of normal bone microarchitecture in tumor-inoculated as well as naïve mice. Further, estrogen supplementation causes adverse urinary tract effects resulting in mice being sacrificed before the experimental end-point 20 , 23 .…”
Section: Introductionmentioning
confidence: 99%